FOSTERING CYBERSECURITY CONSCIOUSNESS: ASSESSING AWARENESS AMONG STUDENTS AND STAFF IN A TECHNICAL INSTITUTION - Norshadila Ahmad Badela (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This research seeks to assess the level of cybersecurity awareness among both students and staff at Politeknik Mersing by means of a comprehensive survey study. The survey questionnaire encompassed a wide array of topics pertaining to cybersecurity knowledge and practices, ranging from email protocols and password management to recognizing phishing attempts and understanding various security concepts. A total of 136 respondents participated in the survey, offering valuable insights into their cybersecurity habits. The results unveiled a varied level of cybersecurity awareness among the participants, showcasing strengths in certain areas while also highlighting notable gaps in others. Particularly, the findings shed light on concerning behaviours such as the tendency to open emails from unfamiliar sources and the practice of using identical passwords across different platforms. These discoveries underscore the critical need for implementing thorough cybersecurity awareness initiatives at Politeknik Mersing, aimed at bridging the identified disparities and promoting safe online conduct. Tailored educational campaigns and continuous training initiatives are recommended to bolster cybersecurity knowledge and instil responsible behaviours. By fortifying cybersecurity awareness, Politeknik Mersing can effectively safeguard sensitive data and mitigate the inherent risks posed by cyber threats. It is advisable to conduct further research to assess the efficacy of specific cybersecurity education interventions and their enduring impact on individuals’ attitudes and behaviours.